Intensive care nurses' knowledge, attitudes and practices of oral care for patients with oral endotracheal intubation - Tembo, Esther (My University, 2016)
Oral hygiene is the basic nursing care activity that promotes health, comfort and pleasant environment that everyone needs. Studies have shown that oral care is not only influenced by knowledge but also the characteristics of the environment. Providing effective oral hygiene in ICU can be challenging due to patient’s medical conditions, treatment, equipment and consciousness level of these critically ill patients. Oral care that is evidence based has proved to overrule this challenge. Studies have shown that the mouth of critically ill patients become colonized with bacteria within 48 hours of admission (Garcia et al. 2009; Grap et al. 2009; Sole et al. 2002). Evidence-based oral care interventions can assist in the prevention of colonization of the mouth by bacteria capable of causing serious and often fatal respiratory infections, such as ventilator associated pneumonia. The purpose of this study was to investigate ICU nurses knowledge, attitudes and practices related to oral care for intubated patients with the associated factors of the same. The intention of the study was also to make recommendations for clinical practice and education of ICU nurses. A non-experimental, quantitative, descriptive and cross-sectional design was used to evaluate ICU nurses knowledge, attitudes and practices regarding evidence-based guidelines and recommendations about oral care for intubated critically ill patients. Data were collected from ICU nurses who were purposively selected using a validated questionnaire (Lin, Chang, Chang and Lou, 2011) to obtain the quantitative results on their knowledge, attitudes and practices of oral care for intubated patients. Data analysis was done by means of descriptive and inferential statistics using graphs, frequency distributions, means and standard deviations and Spearman’s rank order correlation coefficient (rho) and Kruskahl Wallis H test. Testing was done at the 0.05 level of significance. The knowledge, attitudes and practices of 81 nurses working in 5 adult ICUs from one university-affiliated, public sector hospital and tertiary level institution in Johannesburg was tested using the data collection instrument. Knowledge, attitude and practices of trained ICU nurses working in the ICUs were found to be lacking in the evidence-based practice guidelines and recommendations. Of the 81 participants, the mean score for knowledge, attitudes and practices were 31.84%, 60.02% and 52.25%, respectively. A higher level of qualification and years of intensive care experience were not significant factors related to knowledge and the frequency of performing oral care. Although, ICU nurses learning from multiple sources about oral care will improve knowledge and increase the frequency with which they provide oral care for patients. In this study, the correlation coefficients were small; therefore the implications of these findings should be viewed with caution. Overall the findings show that ICU nurses lack knowledge on best practice in the implementation of oral care for patients with endotracheal intubation. Recommendations to address this lack of knowledge were made for ICU nurses to learn more about oral care using a combination of different educational strategies, which will enhance knowledge and improve their practice.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment the requirements for the degree of Master of Science in Nursing Johannesburg, 2016